Gardens in history : a political perspective - Wickham, Louise (Oxford : Windgather, 2012)
Over the past 50 years, the subject of garden history has been firmly established as an academic discipline. While many have explored what was created in gardens throughout history, the reasons as to why they were created has naturally been more diverse. Depending on the background of the author, the ideas have ranged from aesthetic values deriving from art, philosophical thoughts and ideas, social and even economic forces. Occasionally some thought has been given to the influence of political ideology such as the development of the English landscape garden in the first half of the 18th century.
Includes bibliographical references and index.
boek
Keywords: Garden archaeology -- Political aspects; Gardens -- Political aspects; Gardens -- History -- Political aspects; Landscape gardening -- History